Sosialisasi Sex Education: Pentingnya Pengenalan Pendidikan Seks pada Remaja sebagai Upaya Meminimalisir Penyakit Menular Seksual - Farhana Umhaera Patty; Ronald Darlly Hukubun; Sitti Aisa Mahu; Natalia Tetelepta; Linansera, Valentine (Yayasan Literasi Sains Indonesia, 2022)
Sex education is a knowledge that we teach about everything related to gender. This includes starting from the growth of the sex (male or female). How the genitals function as a reproductive device. How the development of the genitals is in women and in men. About menstruation, wet dreams and so on, to the onset of lust due to changes in hormones. Including later marital problems, pregnancy and so on. This activity provides good education to students in the 11th grade of N 10 Ambon High School, we choose high school students because they are in the teenage phase who will grow up. This sex education activity aims to make teenagers know or have a straighter mindset about sex so that they can protect themselves from negative things that will happen.